Pertanggungjawaban Hukum Dan Penetapan Hak Asuh Anak Yang Diterlantarkan Pasca Kematian Salah Satu Orang Tua Di Kota Atambua Berdasarkan Undang-undang Nomor 35 Tahun 2014 Tentang Perubahan atas Undang-undang Nomor 23 tahun 2002 Tentang Perlindungan Anak - Mau, Stefanus; Jacob, Yossie M Y; Pello, Helsina F (Law Faculty, Nusa Cendana University, 2024)
Child custody is the right that parents or guardians have to care for, educate and make important decisions relating to the welfare and development of their child. Child neglect is the act of illegally releasing a person's responsibilities and rights towards their offspring. In this case, the Court and the Women's Empowerment and Child Protection Service (DP3A) play a very important role in the process of accountability for child custody and guaranteeing the child's interests. The type of research used is empirical research. This research was conducted in Atambua City. The types of data used are primary data and secondary data. The data collection technique used was through interviews and observation. The population in this study were judges at the Atambua District Court, employees of the Child Protection Department (DP3A), and parents and guardians of children who were abandoned after the death of their mother in Atambua City. The sample used in this research was saturated sampling, and there were 4 respondents.